The Effect of Generative AI-Based Content Quality on Purchase Intention: A Study on TikTok Users - Muhammad Alfito Danuarta; Ratih Amelia (SAFE-Network, 2026)
This study empirically examines the direct influence of Generative AI and content creation on purchase intention among TikTok users in Indonesia. Grounded in the Stimulus-Organism-Response theory, GenAI and content creation are positioned as digital marketing stimuli that shape consumer behavioral responses. Using a quantitative approach with an explanatory research design, data were collected via an online questionnaire distributed to Generation Z and Millennial users in East Java who had been exposed to AI-assisted promotional content on TikTok. A total of 169 valid respondents were obtained through purposive sampling. Multiple linear regression analysis was employed after confirming validity, reliability, and classical assumption tests. Results indicate that GenAI (β = 0.893, t = 16.673, p < 0.001) and content creation (β = 0.357, t = 5.088, p < 0.001) both significantly and positively influence purchase intention, explaining 78.3% of its variance (Adjusted R² = 0.783). GenAI emerged as the dominant predictor (Beta = 0.737). This study contributes to the digital marketing literature by simultaneously testing two variables previously examined in isolation within the short-video platform context of TikTok.